Respuesta :

Answer:

g(x) already has the slope, 2, so we need to find the slope for f(x)

m=y2-y1/x2-x1

-6-(-12)=6

0-(-1)=1

6/1=6

f(x) has a steaper slope than g(x)

now the y-intercept

g(x) already has the y-intercept, 6, so we need t find the y-intercept fo f(x)

I'll use point-slope form to find it y=m(x)=b

-12=6(-1)=b

6*(-1)=-6

now we want to isolate the b

-6+6=0

-12+6=(-6)

b=-6

g(x) has a greater y-intercept than f(x)

hope this helps :3

Answer:

Give him/her brainliest pls!

Step-by-step explanation:

he should get brainliest